Uloga crkve u integracijskim procesima - Polegubić, Adolf (Array, 2008)
Judging from the words spoken by Monsignor Wolfgang Miehle, the head of the pastoral department for Catholics of other mother tongues at the German Bishop's Conference, at an annual meeting of pastoral workers from western Europe held in Bad Honnef from 8 to 11 October of this year, a new period in the activity of Croatian Catholic missions has already begun in collaboration with the local church. That fact should be taken seriously and actions should be undertaken with others who hold different views with an open mind, especially in cooperation with the local (German in Germany) church. According to the statistical data received in March of 2006 from the Directorate of the Pastoral Department for Croatians abroad in Zagreb, there were 169 Croatian Catholic mission around the world. The majority are, of course, in Germany (78 missions), while Canada has 18, the USA 17, Australia 14, Switzerland 13, Austria 8, Sweden 4, Slovenia and France 3 each and Argentina and Belgium have 2 each. The South African Republic, Luxembourg, the Netherlands, Norway, New Zealand, Peru and Great Britain each have one Croatian Catholic mission. There are 216 priests active in these missions, 127 of which come from the Croatian Bishop's Conference, 83 from the Bishop's Conference of Bosnia & Herzegovina, and three from the Bishop's Conference of the Saints Cyril and Methodius. The institution that coordinates the activities of the missions in Germany is the Croatian Pastoral Office based in Frankfurt am Main. The Reverend Bebić currently heads the office